2012
DOI: 10.1371/journal.pone.0031422
|View full text |Cite
|
Sign up to set email alerts
|

Trastuzumab Produces Therapeutic Actions by Upregulating miR-26a and miR-30b in Breast Cancer Cells

Abstract: ObjectiveTrastuzumab has been used for the treatment of HER2-positive breast cancer (BC). However, a subset of BC patients exhibited resistance to trastuzumab therapy. Thus, clarifying the molecular mechanism of trastuzumab treatment will be beneficial to improve the treatment of HER2-positive BC patients. In this study, we identified trastuzumab-responsive microRNAs that are involved in the therapeutic effects of trastuzumab.Methods and ResultsRNA samples were obtained from HER2-positive (SKBR3 and BT474) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
85
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(92 citation statements)
references
References 38 publications
7
85
0
Order By: Relevance
“…Low serum level of miR-30d is associated with improved prognosis and overall survival in NSCLC (40). The upregulation of miR-30 plays biologic roles in cellular senescence (41) and trastuzumabinduced cell growth arrest (19). In together with our findings, these may suggest combined effects of miR-30s on both primary tumors and distant organs, resulting in the inhibition of tumor proliferation, intravasation, and extravasation.…”
Section: Discussionsupporting
confidence: 70%
“…Low serum level of miR-30d is associated with improved prognosis and overall survival in NSCLC (40). The upregulation of miR-30 plays biologic roles in cellular senescence (41) and trastuzumabinduced cell growth arrest (19). In together with our findings, these may suggest combined effects of miR-30s on both primary tumors and distant organs, resulting in the inhibition of tumor proliferation, intravasation, and extravasation.…”
Section: Discussionsupporting
confidence: 70%
“…According to Ichikawa et al, the genome amplification of the HER-2 receptor is high, but the expression of this receptor is poor in SKBR-3 in comparison to . 27 This could justify our results that showed a decreased expression of let-7a and …”
Section: Discussionsupporting
confidence: 63%
“…12,25,26 It has been demonstrated that the pattern of miRNA expression can be changed in response to treatment with doxorubicin, 5-fluorouracil and trastuzumab, and this alteration can be useful for predicting the outcome of the therapy. [26][27][28] However, there is no clear knowledge of the molecular mechanism of paclitaxel with regards to its effect on miRNAs expression. For that reason, we aimed in this study to evaluate the expression level of 2 tumor-suppressor miRNAs, let-7a and miR-205, before and after treatment with paclitaxel.…”
Section: Discussionmentioning
confidence: 99%
“…Ichikawa et al also found that miR-26a and miR-30b mediate the effects of trastuzumab. 79,80 Furthermore, Iorio et al 81 demonstrated that miR-205, which targets HER3 and impairs the downstream Akt-mediated survival pathway, not only has an oncosuppressive role in breast cancer, but also increases its responsiveness to lapatinib and gefitinib.…”
Section: Mirna In Hormone Receptor-positive/her2-negative Breast Cancermentioning
confidence: 99%